STRATEGI PEMBANGUNAN PRASARANA DAN SARANA PERKOTAAN KAWASAN ANDALAN KOTA PALOPO PROVINSI SULAWESI SELATAN - -, Indrajaya (Jurnal Ilmiah Ecosystem, 2020)
The results of the analysis of macro urban development strategies focused on the development of the Tanjung Ringgit port as an inter-island port supported by plans to develop a national cross-city road network system in Makassar and Palopo, the development of a transportation terminal waste management in synergy with the management of residential waste, the development of a road network system hierarchical which is supported by an increase in sea transportation services and relocation of landfills supported by increased public awareness and provision of waste transportation facilities throughout all parts of the urban area. The micro development strategy of the urban area is focused on the development of industrial and tourism areas which are followed by land price control to support the development of the Tanjung Ringgit port, the arrangement of the city area which is followed by controlling the development of slum areas, improvement of the drainage network system, followed by the development of the road network to the area and providing infrastructure and facilities for drinking water services that are followed by control of environmental pollution in urban areas.